Diabetes and hypertension in patients with psoriasis: a cross sectional and case control study in a tertiary care hospital of Bangladesh - Jamal, Samira; Karim, Sheikh Anwarul; Raihan, Sheikh Mahee Ridwan; Biswas, Rajat; Alam, Mansurul (International Journal of Research in Medical Sciences, 2021)
Background: In this study our main goal was to evaluate the association of psoriasis as a risk predictor for the occurrence of diabetes mellitus (DM) and hypertension (HTN). Methods: This case control study was carried out in the department of dermatology and venereology, Chittagong medical college hospital (CMCH), Chittagong, Bangladesh from 15 June 2011 to 14 May 2012. Where 60 patients with psoriasis and 60 patients with skin diseases other than psoriasis were included according to availability within the study period. Results: During study, among the psoriatic patients, most of the patients with DM and HTN had body mass index (BMI) within normal limit. During analysis of different clinical findings in psoriatic patients scaling was present in all the cases followed by Auspitz sign, koebnerization, itching, scalp involvement and nail changes. Patients with psoriasis were found to have higher incidence of DM and HTN in comparison to their non-psoriatic control group. It was also observed that psoriatic patients having DM and HTN had longer duration of diseases (p<0.05). Conclusions: In conclusion, our study indicates that patients with psoriasis have an increased risk of DM and HTN, confirming the findings from previous several case control and cross sectional studies. These data illustrate the importance of considering psoriasis as a systemic disorder rather than simply a skin disease. Awareness of concurrent diseases will provide the clinician an opportunity of screening .for others systemic diseases.